An Overview on Happy City and Quality of Life related to Environmental Issues - Esmaeili, Samira (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
This thesis aims to review all the factors related to creating a happy city. From basis items, we considered the quality of life that is a multidimensional factor and for evaluating that, we need to observe its subjective and objective criteria. Quality of life has a direct link with well-being and level of happiness. having well-being and feeling happy is the main characteristic of a happy city. As the number of population increase, the number of people who are living in the cities will increase and the quality of urban and their condition should consider as well. In urban, for having happiness and well being, we need to consider the facilities, objective and urban environment. Based on the concept of a happy city that was introduced by Montgomery (2013), there is a link between the quality of life and the urban quality of and happy city. This study by using secondary data and searching about quality of life and its indicators, quality of life and its dimensions and their relationship with happiness, show that how we can create a happy city. In addition, this study by focusing on environmental factors (natural and physical) show that how these indicators play a critical role in our lives and how we can improve and develop our city and transfer them to a happy city for happy people to enjoy their life. In this thesis by comparing the happy city measurements and using some successful cities that are located in the top level of the happy cities in the world, we are going to achieve our goals. The information of this thesis can help urban planners and designers to understand better the role of the natural and physical environment in evaluating the QoL and feeling satisfaction and happiness in urban. This relationship showed that for having a happy city, the physical environment is critical.

ÖZ: Bu tez, mutlu bir şehir yaratmakla ilgili tüm faktörleri incelemeyi amaçlamaktadır. Temel maddelerden çok boyutlu bir faktör olan yaşam kalitesini ele aldık ve bunu değerlendirebilmek için onun subjektif ve objektif kriterlerini gözlemlememiz gerekiyor. Yaşam kalitesi, refah ve mutluluk düzeyi ile doğrudan bağlantılıdır. İyi olmak ve mutlu hissetmek mutlu bir şehrin temel özelliğidir. Nüfus arttıkça şehirlerde yaşayan insan sayısı da artacak ve şehrin kalitesi ve durumu da göz önünde bulundurulmalıdır. Kentte mutluluk ve esenlik için tesisleri, amacı ve kentsel çevreyi göz önünde bulundurmak gerekir. Montgomery (2013) tarafından ortaya atılan mutlu şehir kavramına dayalı olarak, yaşam kalitesi ile mutlu şehrin kentsel kalitesi arasında bir bağlantı vardır. İkincil verileri kullanarak, yaşam kalitesi ve göstergeleri, yaşam kalitesi ve boyutları ve bunların mutlulukla ilişkisini araştıran bu çalışma, mutlu bir kenti nasıl yaratabileceğimizi göstermektedir. Ayrıca, çevresel faktörlere (doğal ve fiziksel) odaklanan bu çalışma, bu göstergelerin hayatımızda nasıl kritik bir rol oynadığını ve şehrimizi nasıl iyileştirip geliştirebileceğimizi ve mutlu insanların hayattan zevk alması için mutlu bir şehre nasıl aktarabileceğimizi göstermektedir. Bu tezde, mutlu şehir ölçümlerini karşılaştırarak ve dünyadaki mutlu şehirlerin en üst seviyesinde yer alan bazı başarılı şehirleri kullanarak hedeflerimize ulaşacağız. Bu tezin bilgileri, kentsel planlamacıların ve tasarımcıların, yaşam kalitesini ve yaşam kalitesini değerlendirmede doğal ve fiziksel çevrenin rolünü daha iyi anlamalarına yardımcı olabilir. Kentsel tatmin ve mutluluk hissetmek. Bu ilişki, mutlu bir şehre sahip olmak için fiziksel çevrenin kritik olduğunu gösterdi.
Master of Science in Urban Design. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2021. Supervisor: Assist. Prof. Dr. Müge Riza.
Keywords: Architecture Department; City planning--Environmental aspects--Sustainable development Planning--Environmental policy--Happy City--Happy Life Streets--Environmental aspects--Urban policy; Environment, Natural Environment, Physical Environment, Urban Life, QoL, Happy City, Urban Quality of Life